Diagnostic potential of sarcoplasmic myxovirus resistance protein A expression in subsets of dermatomyositis. (22nd November 2018) - Uruha, A.; Allenbach, Y.; Charuel, J.‐L.; Musset, L.; Aussy, A.; Boyer, O.; Mariampillai, K.; Landon‐Cardinal, O.; Rasmussen, C.; Bolko, L.; Maisonobe, T.; Leonard‐Louis, S.; et al.
Abstract : Aims: To elucidate the diagnostic value of sarcoplasmic expression of myxovirus resistance protein A (MxA) for dermatomyositis (DM) specifically analysing different DM subforms, and to test the superiority of MxA to other markers. Methods: Immunohistochemistry for MxA and retinoic acid‐inducible gene I (RIG‐I) was performed on skeletal muscle samples and compared with the item presence of perifascicular atrophy (PFA) in 57 DM patients with anti‐Mi‐2 ( n  = 6), ‐transcription intermediary factor 1 gamma ( n  = 10), ‐nuclear matrix protein 2 ( n  = 13), ‐melanoma differentiation‐associated gene 5 (MDA5) ( n  = 10) or ‐small ubiquitin‐like modifier activating enzyme ( n  = 1) autoantibodies and with no detectable autoantibody ( n  = 17). Among the patients, nine suffered from cancer and 22 were juvenile‐onset type. Disease controls included antisynthetase syndrome (ASS)‐associated myositis ( n  = 30), immune‐mediated necrotizing myopathy ( n  = 9) and inclusion body myositis ( n  = 5). Results: Sarcoplasmic MxA expression featured 77% sensitivity and 100% specificity for overall DM patients, while RIG‐I staining and PFA reached respectively 14% and 59% sensitivity and 100% and 86% specificity. In any subset of DM, sarcoplasmic MxA expression showed higher sensitivity than RIG‐I and PFA. Some anti‐MDA5 antibody‐positive DM samples distinctively showed a scattered staining pattern of MxA. No ASS samples had sarcoplasmic MxA expression even though six patients had DM skin rash. Conclusions: Sarcoplasmic MxA expression is more sensitive than PFA and RIG‐I expression for a pathological diagnosis of DM, regardless of the autoantibody‐related subgroup. In light of its high sensitivity and specificity, it may be considered a pathological hallmark of DM per se . Also, lack of MxA expression in ASS supports the idea that ASS is a distinct entity from DM.